Integration of Islamic Ecotheology in Sustainable Mining Management in Indonesia - Syarifuddin Ala Dzil Fikri; Ahmad Nabilul Maram; Abdullah Faqih Hikami (Universitas Islam Negeri Madura, 2026)
This study examines environmental degradation caused by mining activities in Indonesia and proposes an Islamic ecotheological approach as a solution to balance economic interests with ecosystem sustainability. The aim is to analyze how the concepts of human responsibility and justice within religion can be integrated into sustainable mining governance. The methodology employs a qualitative analysis through the thematic interpretation of Qur’anic verses related to environmental ethics, complemented by socio-ecological case studies in several mining regions. Data were collected from official documents, civil society organization reports, and interviews with relevant stakeholders. The findings reveal that water pollution, deforestation, and social conflicts are tangible consequences of irresponsible mining practices, which are exacerbated by corruption, inadequate oversight, and limited local community participation. The Islamic ecotheological approach emphasizes collective responsibility among corporations, the government, and society in maintaining environmental balance. Its implementation includes transparent policies, strict law enforcement, post-mining land rehabilitation, and ecological education grounded in religious values, along with the active involvement of local communities. This study highlights the importance of cross-sector collaboration based on moral values and justice to achieve mining governance that is ecologically, socially, and economically sustainable.